2016
DOI: 10.3141/2541-09
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Analysis of Zones of Tolerance for Transit Service Quality Considering Intelligent Transportation Systems

Abstract: Quality service of public transport is an important issue in transit systems as users' needs and expectations have great relevance in transit modelling and implementation. This explanatory study examines young men and women's expectations and perceptions regarding the transit quality of service by using the concepts of Zone of Tolerance (ZoT) and adequate and desired levels of service. Due to the critical role of Intelligent Transportation Systems (ITS) in public transport service enhancement, specific dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…This paper is primarily concerned with fairness in relation to women, although the concepts and principles can apply to all people. Arabikhan et al [12] argue that providing access to a fair public transport system suited to the needs of women is of particularly importance for those women who they claim have "less access to cars" (p. 80) and are therefore limited in their opportunities for travel. Low access to cars is currently prevalent across many northern European countries [28,37], for many groups (including increasingly the young [15], and suggests that the inclusion of a gendered perspective on future public transport infrastructure and planning is required to provide fair treatment and equality of outcomes for women accessing public transport.…”
Section: Fairness For Whom?mentioning
confidence: 99%
See 2 more Smart Citations
“…This paper is primarily concerned with fairness in relation to women, although the concepts and principles can apply to all people. Arabikhan et al [12] argue that providing access to a fair public transport system suited to the needs of women is of particularly importance for those women who they claim have "less access to cars" (p. 80) and are therefore limited in their opportunities for travel. Low access to cars is currently prevalent across many northern European countries [28,37], for many groups (including increasingly the young [15], and suggests that the inclusion of a gendered perspective on future public transport infrastructure and planning is required to provide fair treatment and equality of outcomes for women accessing public transport.…”
Section: Fairness For Whom?mentioning
confidence: 99%
“…Personal safety has been identified as one of the most importance factors in women's travel decisions, including their perceptions of safety and security whilst accessing, waiting for and travelling using public transport [48]. This may relate to the quality of transport stations, including information provision and waiting times, with, particularly young women feeling less safe than men when waiting at train stations [12]. Chowdhury [49] found that "perceived safety at stations was the only significant variable for female riders" (p. 855), highlighting that fear of crime was a prominent factor in women deciding on whether to use public transport and at what times to do so.…”
Section: Fairness In Transport Used By the Women 41 Public Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Mandhani et al (2021) noted that while evaluating service quality elements, females prioritise "waiting conditions" and "punctuality" whereas males choose "service frequency" and "vehicle cleanliness." In a similar vein, Arabikhan et al (2016) discovered that females have higher expectations and lower perceptions of bus service than males do. Despite strong signs to the contrary, gender imbalance has not been adequately addressed in literature on service quality.…”
Section: Introductionmentioning
confidence: 91%
“…Rider perceptions of bus service have been the subject of several studies, including Arabikhan et al (2016) and Echaniz et al (2018). These studies have shown that changing rider perceptions can significantly enhance service quality, increase transit use, and lessen urban problems.…”
Section: Research Backgroundmentioning
confidence: 99%